2005
DOI: 10.1038/sj.bjp.0706095
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of HERG cardiac K+ current by antifungal drug miconazole

Abstract: 1 Miconazole, an imidazole antifungal agent, is associated with acquired long QT syndrome and ventricular arrhythmias. Miconazole increases the plasma concentration of QT-prolonging drugs by inhibiting the hepatic cytochrome P450 metabolic pathway, but whether it has direct effects on cardiac ion channels has not been elucidated. 2 To determine the mechanism underlying these clinical findings, we investigated the effect of miconazole on human ether-a-go-go-related gene (HERG) K þ channels. 3 HERG channels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…PPB are either from published data (plain text) or measured in our laboratories (bold italics). [22]; c: [23]; d: [24,25]; e: [26]; f: [27]; g: [28]; h: [19]; i: [29]; j: [30]; k: [31]; l: [32]; m: [33]; n: [34]; o: [35]; p: [36]; q: [37]; r: [38]; s: [39]; t: [40]; u: [41]; v: [42]; w: [43]; x: [44]; y: [45]; z: [46]; aa: [47]; bb: [48]; cc: [49]; dd: [50]; ee: [51]; ff: [52]; gg: [53]; hh: [54]; ii: [55]; jj: [56]; kk: [57]; ll: [58]; mm: [59]; nn: [60]; oo: [61]; pp: [62]; qq: [63]; rr: [64]; ss: [65]; tt: [66]; uu: [67]; vv: [68]; ww: …”
Section: Drugs With a Cardiovascular Target Without A Direct Role In mentioning
confidence: 99%
“…PPB are either from published data (plain text) or measured in our laboratories (bold italics). [22]; c: [23]; d: [24,25]; e: [26]; f: [27]; g: [28]; h: [19]; i: [29]; j: [30]; k: [31]; l: [32]; m: [33]; n: [34]; o: [35]; p: [36]; q: [37]; r: [38]; s: [39]; t: [40]; u: [41]; v: [42]; w: [43]; x: [44]; y: [45]; z: [46]; aa: [47]; bb: [48]; cc: [49]; dd: [50]; ee: [51]; ff: [52]; gg: [53]; hh: [54]; ii: [55]; jj: [56]; kk: [57]; ll: [58]; mm: [59]; nn: [60]; oo: [61]; pp: [62]; qq: [63]; rr: [64]; ss: [65]; tt: [66]; uu: [67]; vv: [68]; ww: …”
Section: Drugs With a Cardiovascular Target Without A Direct Role In mentioning
confidence: 99%
“…However, recent studies suggest that azole antifungal agents such as miconazole, ketoconazole, fluconazole, and itraconazole are associated with acquired long QT (LQT) syndrome and ventricular arrhythmias. [1][2][3] Ventricular arrhythmias caused by antifungal agents seem to be related to the human-ether-a-go-go-related gene (HERG) channels. Kikuchi et al 3) reported that the cardiac HERG K + current is inhibited by miconazole.…”
mentioning
confidence: 99%
“…These properties are similar to those of mesoridazine 32) and miconazole. 33) In summary, IM is a potent blocker of HERG channels, and it blocks the channels in a state-dependent manner.…”
Section: Discussionmentioning
confidence: 99%